Transforming our world: How the Sustainable Development Goals will help us achieve zero hunger - Nabarro, David (Welthungerhilfe, 2016)
Given the complex and interconnected nature of the root causes of poverty and of hunger, delivering on the 2030 Agenda provides the best and surest way of getting to Zero Hunger faster. With collaboration at all levels and by utilizing advances in technology, employing innovative approaches, and ensuring that honesty, fairness, and justice are the underpinning principles of all our actions, we can transform our world and eradicate poverty and hunger for all, and for good. The goals are ambitious but by no means impossible. Together we can see this vision transform into reality.